Analysis on the performance of pointing error effects for RIS-aided FSO link over gamma-gamma channels - Duong Huu Ai; Dai Tho Dang; Quang Hien Dang; Trong Le Kim (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2023)
In this study, we analysis on the performance of pointing error effects for reconfigurable intelligent surfeces (RISs) aided free-space optical (FSO) communication link over moderate to strong atmospheric turbulence channels. Among these solutions, RISs are considered as hardware technology to improve performance of optical wireless communication systems. Performance evaluation of systems is affected by atmospheric attenuation, pointing errors and moderate to strong atmospheric turbulence channels for quadrature amplitude modulation (QAM) technique. Atmospheric turbulence channel from moderate to strong is modeled using gamma-gamma distribution. Several numerical results obtained the average symbol error rate (ASER) performance versus beam waist radius and signal to noise ratio for three value of pointing error displacement standard deviation. From the results, it is show that with RIS assisted can effectively improve the performance and link distance of the wireless communication systems.